Faktor-Faktor yang Memengaruhi Kejadian Stunting pada Balita Usia 25-59 Bulan - Sri Lestari Ramadhani Nasution; Ervineco Limestan; Saud Parulian Harianja; Ermi Girsang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the risk factors for stunting in toddlers aged 24-59 months in the working area of Royal Prima Marelan Hospital. The method used is observational with a cross-sectional design. The results showed a relationship between exclusive breastfeeding, complementary breastfeeding, father's height, income and nutritional status with the incidence of stunting in children aged 24-59 months. The level of energy intake, protein intake, and maternal height did not significantly correlate with the incidence of stunting. In conclusion, the father's height factor has the most dominant relationship with the incidence of stunting. Keywords: Toddlers, Risk Factors, Stunting, Parents' Height